The Effect of Pretreatment Temperature in The Mycobacterium tuberculosis Extraction Method on DNA Quality - Setianingsih, Tri Yuli; Fitri, Safira; Wahyono, Daniel Joko; Setiawaty, Vivi (Elkawnie: Journal of Islamic Science and Technology, 2024)
Abstract: The existing DNA extraction process for Mycobacterium tuberculosis employs a pretreatment step that may not function at its full potential. This inefficient process led to complications in subsequent analysis; thus, it is necessary to determine the successful extraction method with or without adding a pretreatment step. This study aims to determine the effect of temperature pretreatment on the extraction method of M. tuberculosis on the quality of DNA for WGS examination. The research design was analytically descriptive with a kit-based extraction method from ExiPrepTM Dx Mycobacteria Genomic DNA Kit (K-4418), Bioneer. The results of this study were that DNA purity did not differ (p = 0.959) between the pretreatment heating at 950 °C (2.88) and no heating at 950 °C (2.46). DNA concentration did not differ (p-value = 0.111) between pretreatment heating 950C (0.416 ng/µL) and no heating 950C (0.653 ng/µL). The relatively low DNA concentration resulted in the DNA bands not being visualized on agarose gel electrophoresis (0.8%). In conclusion, our study showed that the pretreatment heating step on M. tuberculosis DNA extraction does not affect DNA purity, concentration, or integrity. This inefficiency step can be discarded from the M. tuberculosis DNA extraction process to simplify the extraction processing. However, other extraction kit approaches need to be explored in future studies.Abstrak: Proses ekstraksi DNA Mycobacterium tuberculosis yang saat ini dilakukan memerlukan pretreatment yang mungkin tidak berpengaruh secara optimal. Proses yang tidak efisiensi berpengaruh terhadap analisis selanjutnya, sehingga perlu untuk mengetahui keberhasilan metode ekstraksi dengan penambahan proses pretreatment. Tujuan penelitian ini adalah untuk mengetahui pengaruh pretreatment suhu pada metode ekstraksi M. tuberkulosis terhadap kualitas DNA untuk pemeriksaan WGS. Desain penelitian adalah deskriptif analitik dengan metode ekstraksi berbasis kit dari ExiPrepTM Dx Mycobacteria Genomic DNA Kit (K-4418), Bioneer. Hasil penelitian adalah kemurnian DNA tidak berbeda (p=0,959) antara pretreatment pemanasan 950C (2,88) dengan tanpa pemanasan 950C (2,46). Konsentrasi DNA tidak berbeda (p value = 0,111) antara pretreatment pemanasan 950C (0,416 ng/µL) dengan tanpa pemanasan 950C (0,653 ng/µL). Konsentrasi DNA yang relatif rendah mengakibatkan pita DNA tidak tervisualisasi pada elektroforesis gel agarosa (0,8%). Kesimpulan dari penelitian  ini, bahwa langkah pemanasan awal pada ekstraksi DNA M. tuberkulosis tidak berpengaruh terhadap kemurnian, konsentrasi, dan integritas DNA. Langkah ini dapat dihilangkan dari proses ekstraksi DNA M. tuberkulosis untuk menyederhanakan proses ekstraksi. Namun, pendekatan kit ekstraksi lainnya perlu dieksplorasi dalam penelitian selanjutnya